The Micro Dynamics of Macro Announcements - Stefan Mittnik; Nikolay Robinzonov; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2013)
We examine how regularly scheduled macroeconomic announcements for the U.S., Germany and the euro area affect the German stock market, using highfrequency, minutebyminute DAX data. Our study extends the literature on highfrequency announcement effects in several ways. First, we account for endogenous return dynamics by assessing announcement impacts via response analysis. Second, we examine the announcements effects on market volatility in a more detailed fashion by distinguishing effects of positive and negative surprises. Finally, we adapt the standard weightedleastsquares approach to more adequately analyze both conditional mean and volatility effects.
Keywords: F30; F40; G14; C58; 330; announcement effects; market efficiency; information spillover; impulse response analysis; volatility; weighted least squares